مناهج الدراسة اللغوية في التراث العربي - Walfajri Walfajri (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
The human has a strong will to know things around him, particularly the language that distinguishes him from other creatures. So he always sees the language in many kinds of theories and methods of language studies. There are many kinds of methods can be used in the field of modern language studies, such as descriptive method, historical method, comparative method, prescriptive method, and contrastive method. Each of these methods of language studies has limitations, weaknesses, and advantages.So, for the researchers to choose a method or to combine some methods which fit with their research in the field of modern language studies. Keywords: descriptive method, comparative method, contrastive method